Multicentric Study on the Diagnostic of Neuromuscular Diseases in Children with High Creatinine Phosphokinase Levels - Cláudia Monteiro; Cristina Garrido; Ângela Pereira; Andreia Dias; Mariana Costa; Catarina Magalhães; Manuela Ferreira; Miguel Costa; Manuela Santos (Children)
Background: Neuromuscular diseases (NMDs) are rare, predominantly hereditary, with progressive course disorders. Furthermore, diagnosis can be delayed by years after symptoms emerge, resulting in missed opportunities for modifying disease progression, specific therapeutic approaches, and counseling. Some NMDs have high levels of creatine phosphokinase (CK). Thus, its measurement can indicate an NMD associated with muscle involvement. Objectives: We aimed to identify myopathies and muscular dystrophies through elevated CK levels for early detection of these disorders. Methods: A prospective, observational, and analytical study of children and teenagers showing high levels of CK, showing mild symptoms, or who were asymptomatic with elevation of transaminases from all pediatric units in the north of Portugal was performed. All diagnosed patients were referred to our Center for Neuromuscular Diseases. Additionally, CK level confirmation, clinical examination, and investigation were performed according to best-practice clinical guidelines. Results: We found 33 patients from 8/12 pediatric units. A diagnosis with implications for care measures and treatment was performed in half of the patients. A total of 30% presented an NMD diagnosis. Dystrophinopathies represented the largest group (21%). Conclusions: Therefore, NMDs should be considered in children and teenagers with high CK levels, even those with mild symptoms. Screening for CK elevation should be used to promote an earlier diagnosis of many NMDs.